Changes in atmospheric composition during the 2014 APEC conference in Beijing. Issue 24 (17th December 2015) - Wang, Zhanshan; Li, Yunting; Chen, Tian; Li, Lingjun; Liu, Baoxian; Zhang, Dawei; Sun, Feng; Wei, Qiang; Jiang, Lei; Pan, Libo
Abstract: Five sites were selected to investigate the impact of regional‐scale air pollutant control strategies during the Asia‐Pacific Economic Cooperation (APEC) conference (1–12 November 2014) in and around Beijing. Concentrations of most of the air pollutants in the APEC period were significantly lower than those in the adjacent time period, especially when the enhanced reduction measures were implemented. Compared with the same time period in the previous 5 years (PM2.5 was compared with the last year), average concentrations of SO2, NO2, PM10, and PM2.5 in the five sites during the APEC period decreased by 62%, 41%, 36%, and 47% respectively, whereas average concentration of O3 increased by 102%. A possible cause of the increase of O3 concentrations is the stricter reduction measure on NO x compared to that applied to volatile organic compounds. Compared with the non‐APEC period in autumn 2014, concentrations of most of the chemical compositions of PM2.5 decreased significantly in the APEC period, especially SO4 2−, NO3 −, and NH4 + (sulfate, nitrate, and ammonium). The aerosol optical depth and the columnar NO2 in the area of 39.5°–40.5°N, 116°–117°E showed a changing pattern similar to the typical gas pattern. The net effectiveness of the emission reduction measures was calculated through a comparison of concentrations of air pollutants under similar meteorological conditions. Through the reduction measures imposed during the APEC period, concentrations of CO, SO2, NO, NO2, PM10, and PM2.5 decreased by 54%, 74%, 64%, 48%, 67%, and 65%, respectively, whereas concentrations of O3 increased by 189%. Key Points: Concentrations of most of the air pollutants decreased, whereas concentrations of O3 increased The impact was more significant in diurnal variation when meteorological conditions were favorable The accumulation of PM2.5 slowed down under unfavorable meteorological conditions